Posts by Karoline
Total # Posts: 5
Differentiate using the product rule. How do i get from dy/dx = d(uv)/dx = u dv/dx + v du/dx =(5x-2)^3[-6(3-x)^5]+(3-x)^6[15(5x-2)^2] to: =(5x-2)^2(3-x)^5(-30x+12+45-15x) it's an example taken from my text book. Could you help me? thank you!
hey sorry, one more thing. How do you find -3 as in now I see the following common factors -3 how ?
ah OK, now i get it. Thank you so much!!
thanks! there is an example here and where i get lost is a step where it goes from dy/dx = d(uv)/dx = u dv/dx + v du/dx = (5x-2)^3[-6(3-x)^5]+(3-x)^6[15(5x-2)^2] = (5x-2)^2(3-x)^5(-30x+12+45-15x) is there a step between there that you could show me how to do so i can ...
Differentiate y=(5x-2)^3(3-x)^6 using the product rule. i don't get the step where they find the common factor could you help me by doing it step by step please ? thank you!